(untitled) (Journal of Computational Mathematics, 1998)
In this paper, we have obtained an expression of the bivariate Vandermonde determinant for the Elliptic Type Node Configuration in R^2, and discussed the possibility of the corresponding multivariate Lagrange, Hermite and Birkhoff interpolation.